Elevated serum progesterone levels on the hCG trigger day have a negative impact on the live birth rate in the first fresh IVF-ET cycle. (17th November 2022) - Jiang, Weihua; Li, Dong; Zhu, Lihua; Wang, Jie; Chen, Linjun; Zhang, Ningyuan; Wang, Shanshan
Abstract: To investigate whether there is a relationship between elevated serum progesterone (PROG) on the hCG trigger day and the live birth rate (LBR) in IVF/ICSI cycles, the retrospective analysis was carried out from the patients undergoing the first ART cycles throughout 2016. The PROG levels were measured on the hCG trigger day. The LBR, clinical pregnancy rate (CPR), implantation rate (IR) and other parameter rate values were compared among the three different PROG elevations. A total of 2550 IVF/ICSI cycles fulfilling all the inclusion and exclusion criteria were selected. Finally, three groups [PROG <0.40 ng/mL, 0.40 ≤ PROG < 1.5 ng/mL, PROG ≥ 1.5 ng/mL] were categorised based on the serum PROG levels. LBR, CPR and IR declined as the PROG value increased, while there was no difference in the embryo utilisation rates. Serum PROG levels on the day of hCG administration were negatively associated with the LBR, even in ETs with a good prognosis. Impact Statement: What is already known on this subject? The clinical effects of PROG are still controversial. Some studies have confirmed that there was not too much association between premature elevation of PROG and live birth, some are still convincing that there is a negative correlation and will result in ART cycles of pregnancy and LBR reduction. What do the results of this study add? Our data substantiated that the high serum PROG level had the lowest LBR, IR and CPR, but the embryo utilisation rate may not have too much to do with the elevated PROG. What are the implications of these findings for clinical practice and/or further research? This study further strengthens the negative impact of elevated PROG levels on pregnancy outcomes, and suggests that frozen thawed embryo transfer appears to be a reasonable and advantageous approach for this subset of patients.